2013
DOI: 10.1074/jbc.m113.475343
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Induces Hypothalamic Endoplasmic Reticulum Stress and Impairs Proopiomelanocortin (POMC) Post-translational Processing

Abstract: Background:The ␣-MSH peptide is essential in regulating food intake and energy expenditure. Results: ER stress induced by obesity reduces ␣-MSH, accumulates POMC, and decreases the enzyme PC2. Conclusion: There is a direct link between obesity and ER stress, resulting in altered POMC processing. Significance: These studies bring a new perspective to how ER stress can regulate energy balance by altering POMC processing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
99
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(103 citation statements)
references
References 70 publications
2
99
0
2
Order By: Relevance
“…Both the 48-h and 2-wk HFD-treated groups also exhibited trends for decreased levels of all POMC peptides, with the decrease in ACTH after the 48-h HFD (P Ͻ 0.05) and ␤-endorphin levels after chronic HFD (P Ͻ 0.05) reaching significance. Neither acute nor 2 wk leptin treatments significantly modified the individual POMC peptide levels, but there were slight changes in the molar ratio of ACTH/␣-MSH consistent with alterations in POMC peptide processing (8,50).…”
Section: E909 Leptin-independent Diet Effects On Pomc Peptidesmentioning
confidence: 83%
See 2 more Smart Citations
“…Both the 48-h and 2-wk HFD-treated groups also exhibited trends for decreased levels of all POMC peptides, with the decrease in ACTH after the 48-h HFD (P Ͻ 0.05) and ␤-endorphin levels after chronic HFD (P Ͻ 0.05) reaching significance. Neither acute nor 2 wk leptin treatments significantly modified the individual POMC peptide levels, but there were slight changes in the molar ratio of ACTH/␣-MSH consistent with alterations in POMC peptide processing (8,50).…”
Section: E909 Leptin-independent Diet Effects On Pomc Peptidesmentioning
confidence: 83%
“…By contrast, a surplus of calories from fat or an exogenous injection of the fat-derived adipokine leptin have been reported to increase transcription of Pomc and the synthesis of POMC peptides (25,34,45,50,62,70). However, extended bouts of high-fat diet (HFD) are also reported to diminish the expression of POMC peptides and the conversion of ACTH to ␣-MSH (8,17,39,63). Likewise, diet-dependent changes in POMC peptide levels are also conferred, at least in part, by tandem regulation of peptide cleavage and peptide-modifying enzymes (8,25,46).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Corroborating this theory, preclinical studies found that specific overexpression of molecular ER components can prevent dietary inhibition of leptin signalling [22]. Accordingly, pharmacological application of the chemical chaperones tauroursodeoxycholic acid (TUDCA) and 4-phenyl butyric acid (4-PBA) can alleviate hypothalamic ER stress to reverse diet-induced leptin resistance [22][23][24]. These chemical chaperones stabilise protein folding by decreasing the formation of abnormal protein aggregates, which reduces ER stress.…”
Section: Targeting Leptin Responsiveness With Pharmacologymentioning
confidence: 99%
“…An imbalance between the loading and folding capacities of the ER results in a condition known as ER stress. Pioneering studies have demonstrated a causal link between hypothalamic ER stress, leptin signalling and obesity [22,23] (Fig. 1).…”
Section: Targeting Leptin Responsiveness With Pharmacologymentioning
confidence: 99%